2018
DOI: 10.1111/srt.12617
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive profiling of sweat‐derived lipid mediators for cutaneous research

Abstract: Sweat metabolites may be capable of reporting changes in cutaneous biochemical pathways, thereby providing insight into the immunomodulatory biochemistry of the skin. Lipid mediator analysis of sweat appears to be a non invasive approach that could enhance existing cutaneous research and diagnostic methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Studies on the composition of free SBs in AD are scarce. Agrawal et al [26] found increased levels of sphingosine in the sweat of AD patients, however contrary to these results Arikawa et al [27] reported decreased sphingosine levels in the lesional and non-lesional skin of AD patients.…”
Section: Discussionmentioning
confidence: 87%
“…Studies on the composition of free SBs in AD are scarce. Agrawal et al [26] found increased levels of sphingosine in the sweat of AD patients, however contrary to these results Arikawa et al [27] reported decreased sphingosine levels in the lesional and non-lesional skin of AD patients.…”
Section: Discussionmentioning
confidence: 87%
“…Julia Oh 85 compared metabolites derived from differing skin sites and emphasized the marked variation between individuals. Others explored the potential importance of measuring sweat metabolites in studies of the skin 86 . None of these studies focused specifically on obesity or the ethnicity of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Others explored the potential importance of measuring sweat metabolites in studies of the skin [80]. None of these studies focused specifically on obesity or the ethnicity of the subjects.…”
Section: The Most Detailed Previous Evaluation Of Differences Betweenmentioning
confidence: 99%